Role of Women in Disaster Management: An Assessment Study in Kurigram and Patuakhali Districts of Bangladesh - Mahbub, Hossain Al; Jamal, Samrina; Rahman, Mijanur; Muhibbullah, Muhammad (Journal of Geosciences and Environmental Studies, 2025)
Women are the most marginalized and vulnerable to disasters due to disadvantaged socio-economic status and unequal access to resources in Bangladesh. Common perceptions paint women as dependent, weak, incapable, and subordinate, viewing them as burdens, which keeps them isolated from the mainstream processes of society, like planning and decision-making. The present study was conducted in the Kurigram and Patuakhali districts of Bangladesh. It aimed to explore women's role in disaster management, focusing on the nature of their involvement and different social factors that influence women's participation. Primary data were collected through 203 questionnaires from two districts, and 4 FGDs were conducted to validate and cross-check the data obtained from the questionnaires. 2 Expert opinion surveys have been conducted in the study area. The data reveals the present condition of women's participation in disaster management processes and their undervalued contribution in different stages, different factors influencing their active participation, the evolution and future perspectives about their involvement in disaster management. Participants reported that a lack of educational awareness programs and work independence hinder their active participation in disaster management.  Findings highlight a significant gap regarding the current gender responsive disaster management policies. The result highlights that it is necessary to ensure their contributions are recognized at all levels of disaster management.